Regression Modeling of Zero-Inflated Negative Binomia (ZINB) in Pneumonia Cases in Toddlers in North Sumatra Province - Hasibuan, Hani Maulida; Husein, Ismail (Information Technology and Science (ITScience), 2025)
Pneumonia is a lung infection that causes inflammation in the air sacs within the lungs. This disease is caused by microorganisms such as bacteria, viruses, fungi, or even inhaled substances. This study aims to identify significant factors influencing the incidence of pneumonia in children under five years old in North Sumatra Province in 2022. In this case, the dependent variable has an excessive number of zero values (excess Zero), leading to overdispersion. By using the Zero Inflated Negative Binomial (ZINB) regression method, significant factors affecting the incidence of pneumonia in children under five years old in North Sumatra Province were identified. The study found that the variable of the number of low birth weight babies (BBLR) (X5) significantly influences the incidence of the disease in North Sumatra Province in 2022. It can be seen from the significant variables affecting the occurrence of pneumonia in children under five, which are 0.0406% (X1), 0.00952% (X2), 0.006506% (X3), and 2.122% (X4).